POLA KOMUNIKASI DALAM SANGKEPAN DESA ADAT PENGLIPURAN KECAMATAN BANGLI KABUPATEN BANGLI - I Dewa Ayu Komang Raka Dharmayanti; Relin D.E; I Nyoman Ananda (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2024)
Traditional village leaders, in this case kelian desa, are the main authorities in managing traditional villages in Penglipuran traditional village, Kubu sub-district, Bangli sub-district, Bangli district, so they need to have innovative capabilities and initiative in leading their traditional villages. In this regard, effective communication efforts are also implemented in the traditional Penglipuran village, especially in the customary decision-making process which is carried out through deliberations for consensus in a traditional village meeting or better known as the traditional village pesantren, with the hope that what is planned, discussed and decided in sangkepan can make society harmonious, peaceful gemah ripah loh jinawi kerta raharje.Based on this background, the researcher is interested in researching "Patterns of Communication in Sangkepan at Penglipuran Traditional Village, Bangli District, Bangli Regency", with the formulation of the problem, namely 1) What are the communication patterns in traditional sangkepan at Penglipuran Traditional Village, Bangli District, Bangli Regency? 2) What are the decision-making systems and constraints in traditional sangkepan at Penglipuran Traditional Village, Bangli District, Bangli Regency?3) What are the implications of communication patterns in traditional sangkepan at Penglipuran Traditional Village, Bangli District, Bangli Regency? The results of the study show that: 1) The communication patterns applied in the sangkepan in Penglipuran traditional village are group communication patterns and star communication patterns. 2) The decision-making system in sangkepan is deliberation for consensus and the factors that become obstacles in the decision-making process are internal and external factors. 3) The implications/impacts resulting from the application of communication carried out by the village head as the traditional leader in the Penglipuran customary village are changes in the cognitive (knowledge), affective (attitude) and psychomotor aspects in the form of: increasing awareness of indigenous peoples about the importance of communicating effectively good and directed as well as growing a sense of openness in the sangkepan. This research is expected to provide academic insight to students as well as material for comparison between theory and reality in the field regarding communication patterns in traditional sangkepan. For traditional village prajuru to take strategic steps to overcome the obstacles that exist in the application of communication patterns that take place with customary village residents. Keywords: communication pattern, sangkepan